France's Africa policy under president Macron: Good intentions, partial reform and the fiasco in the Sahel - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2023)
Since his election in 2017, President Emmanuel Macron has tried to distance himself from established and widely criticised patterns of France's Africa policy. He diversified relations with Africa in regional and substantive terms, integrated non-state actors and cultivated a comparatively open approach to France's problematic past on the continent. However, Macron's efforts to craft a narrative of change was overshadowed by path dependencies, above all the continuation of the military engagement in the Sahel and incoherent relations with autocratic governments. The involuntary military withdrawal first from Mali (2022), from Burkina Faso (2023) and finally from Niger (announced for late 2023) marks a historic turning point in Franco-African relations. The question is no longer whether relations between France and its former colonies will change; the real question is whether Paris will be able to shape this change or if it will be a mere bystander to a transformation that is largely driven by African actors.
Keywords: 320; Frankreich; Emmanuel Macron; Burkina Faso; Côte d’ Ivoire; Dschi buti; Mali; Senegal; Tschad; Afrikapolitik; entwicklungs politische Zusammenarbeit; Agence française de développement; AFD; Frankophonie; Françafrique; Pré-carré; Public Diplomacy; Opérations extérieures; OPEX; Opération Barkhane; Opération Serval; Franc CFA; Union économique et moné taire ouest-africaine; UEMOA; Economic Community of West African States; ECOWAS; Banque Centrale des États de l’ Afrique de l’ Ouest; BCEAO; France’ s Africa policy; Franco-African relations; Emmanuel Macron; Sahel; Mali; Burkina Faso; Niger; Union économique et monétaire ouest-africaine (UEMOA); Economic Community of West African States (ECOWAS); official development assistance (ODA); Operation Barkhane